Development of STEM-Based E-LKPD on Pythagorean Theorem Material on Students' Problem-Solving Ability - Oktaviani Silaen, Elza; Susanti, Ely; Aisyah, Nyimas (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Problem-solving ability is a critical component of mathematics education, particularly in understanding Pythagorean theorem concepts. However, current instructional practices often lack integration of STEM approaches and interactive digital tools that support the development of this ability. This study aimed to develop a valid, practical, and potentially effective STEM-based Electronic Student Worksheet (E-LKPD) to enhance students’ problem-solving ability. The research employed the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation) and involved expert validation, practicality testing, and effectiveness assessment with eighth-grade students in a public junior high school following the Merdeka Curriculum. Data were collected through expert validation sheets, student practicality questionnaires, and problem-solving ability tests, then analyzed using descriptive statistics. Results showed that the E-LKPD met validity criteria with an average score of 4.20, reached a practicality level of 85.33%, and demonstrated a positive potential effect, with 57.71% of students achieving a good performance in problem-solving ability. These findings indicate that the developed STEM-based E-LKPD aligns with pedagogical and technological requirements and is suitable for implementation in mathematics learning contexts. This study contributes to digital mathematics pedagogy by offering a contextual STEM-based learning tool supported by interactive technology, addressing current needs in technology-integrated instruction. Abstrak Kemampuan pemecahan masalah merupakan komponen penting dalam pembelajaran matematika, khususnya pada pemahaman konsep Teorema Pythagoras. Namun, praktik pembelajaran saat ini masih kurang dalam mengintegrasikan pendekatan STEM dan alat digital interaktif yang mendukung pengembangan kemampuan ini. Penelitian ini bertujuan untuk mengembangkan Lembar Kerja Peserta Didik Elektronik (E-LKPD) berbasis STEM yang valid, praktis, dan berpotensi efektif untuk meningkatkan kemampuan pemecahan masalah siswa. Penelitian menggunakan model pengembangan ADDIE (Analyze, Design, Development, Implementation, dan Evaluation) serta melibatkan validasi ahli, uji kepraktisan, dan uji efektivitas terhadap siswa kelas VIII di salah satu SMP negeri yang menerapkan Kurikulum Merdeka. Data dikumpulkan melalui lembar validasi ahli, angket kepraktisan, dan tes kemampuan pemecahan masalah, kemudian dianalisis secara deskriptif. Hasil menunjukkan bahwa E-LKPD memenuhi kriteria valid dengan skor rata-rata 4,20, tingkat kepraktisan sebesar 85,33%, dan menunjukkan potensi efektivitas, dengan 57,71% siswa mencapai kategori baik dalam kemampuan pemecahan masalah. Temuan ini menunjukkan bahwa E-LKPD berbasis STEM yang dikembangkan telah sesuai dengan kebutuhan pedagogis dan teknologi, serta layak diterapkan dalam pembelajaran matematika. Penelitian ini berkontribusi terhadap pedagogi digital matematika melalui penyediaan alat pembelajaran kontekstual yang mengintegrasikan prinsip STEM dan teknologi interaktif.